Local endocytosis of sucrose transporter 2 in duckweed reveals the role of sucrose transporter 2 in guard cells - Liu, Penghui; Fang, Yang; Tan, Xiao; Hu, Zhubin; Jin, Yanling; Yi, Zhuolin; He, Kaize; Wei, Cuicui; Chen, Rui; Zhao, Hai (Frontiers in Plant Science, 2022)
The local endocytosis of membrane proteins is critical for many physiological processes in plants, including the regulation of growth, development, nutrient absorption, and osmotic stress response. Much of our knowledge on the local endocytosis of plasma membrane (PM) protein only focuses on the polar growth of pollen tubes in plants and neuronal axon in animals. However, the role of local endocytosis of PM proteins in guard cells has not yet been researched. Here, we first cloned duckweed SUT2 (sucrose transporter 2) protein and then conducted subcellular and histological localization of the protein. Our results indicated that LpSUT2 (Landoltia punctata 0202 SUT2) is a PM protein highly expressed on guard cells. In vitro experiments on WT (wild type) lines treated with high sucrose concentration showed that the content of ROS (reactive oxygen species) in guard cells increased and stomatal conductance decreased. We observed the same results in the lines after overexpression of the LpSUT2 gene with newfound local endocytosis of LpSUT2. The local endocytosis mainly showed that LpSUT2 was uniformly distributed on the PM of guard cells in the early stage of development, and was only distributed in the endomembrane of guard cells in the mature stage. Therefore, we found the phenomenon of guard cell LpSUT2 local endocytosis through the changes of duckweed stomata and concluded that LpSUT2 local endocytosis might be dependent on ROS accumulation in the development of duckweed guard cells. This paper might provide future references for the genetic improvement and water-use efficiency in other crops.